ANALYSIS OF TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY ASSAY OF GUAVA VARIETY CRYSTAL (Psidium guajava L.) LEAVES EXTRACT - Tarigan, Dewi Br; Lenny, Sovia; Zuhra, Cut Fatimah (Jurnal Kimia Riset, 2024)
The study investigates the antioxidant activity and total flavonoid compounds in leaves crystal guava, a plant rich in vitamin C and high in antioxidant activity. The research involved maceration extraction of leaves cystal guava using methanol solvent, then fractionation with ethyl acetate and n-hexane solvents in stages to obtain extracts methanol, ethyl acetat and n-hexane; thereafter extracts were subjected to phytochemical screening, total flavonoid content determination, and antioxidant activity using the DPPH method. The study found secondary metabolite compounds which is found in leaves crystal guava such as flavonoids, alkaloids, steroids, terpenoids, saponins and tannins; that ethyl acetate extract had the highest flavonoid content of 171.91 mg/L and highest antioxidant activity with IC50 value of 9.59 ppm, followed by n-hexane and methanol extracts.